Membongkar Mitos Kepuasan Pelanggan dan Mutu Layanan: Studi Kualitatif Kritis pada Industri Perhotelan di Era Digital - Agus Hermawan; Asep Nur Imam Munandar (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
This study is motivated by the dominance of the customer satisfaction paradigm that treats service quality as an objective and measurable reality. In the hospitality industry, such a paradigm often produces a myth of satisfaction that conceals the social and emotional dynamics behind service delivery. The research aims to uncover the social construction underlying the myth of customer satisfaction in five-star hotels in the digital era. Using a qualitative approach with critical discourse analysis, the study draws on in-depth interviews, passive participatory observations, and documentation involving management, staff, and guests. The findings reveal four key mechanisms sustaining this myth: the contested meanings of “quality” among stakeholders, the staging of flawless service that masks emotional labor, the illusion of equal treatment that hides guest segmentation, and the ritualization of measurement centered on digital metrics. The study concludes that satisfaction should be viewed as a socially negotiated cultural artifact rather than a mere numerical indicator. These findings enrich critical service management studies and highlight the need to balance performance metrics with employee well-being.